Thyroid Adenoma of Probable Ultimobranchial Body Origin: A Case Report. (April 2021) - Yuen, K. K. W.; Chan, A. N. H.; Chan, J. K. C.; Cheuk, W.
Solid cell nests are generally believed to represent remnants of the ultimobranchial body, which can be found in the normal thyroid gland, occasionally associated with other branchial pouch remnants such as salivary gland, cartilage, and adipose tissue. We describe the case of a 44-year-old man incidentally found to have a large tumor in the left lobe of the thyroid. The tumor was a circumscribed growth consisting of distinctly lobulated proliferation of solid to cystic epidermoid cell nests and thyroid follicles in a fibromatous stroma, which merged into abundant adipose tissue and focally myxoid matrix. The solid epidermoid cell nests resembled solid cell nests and exhibited a p63+, GATA3+, galectin-3+, TTF1−, PAX8−, thyroglobulin− phenotypes, while the follicles were p63−, GATA3−, galectin-3−, TTF1+, PAX8+, and thyroglobulin+. RAS mutations were not found. This thyroid tumor may represent a hitherto undescribed "ultimobranchial body adenoma" in human.